ANALYSIS OF COMPLICATIONS AFTER LAPAROSCOPIC CHOLECYSTECTOMY - TashtemirovаOlga; Apseyev, Marat (European Scientific Journal, ESJ, 2014)
The detailed analysis of 561 operations performed laparoscopic cholecystectomy (LCE) and their complications. Concluded that during this period LCE became the operation of patients’ choice with a benign gall bladder diseases, and the key to a successful implementation of LCE are good technical equipment of operating room, highly professional preparation of surgeons performing laparoscopic surgery, a meticulous preoperative examination of patients, strict adherence to the rules of performing laparoscopic surgery and attentive postoperative supervision of patients.